2021
DOI: 10.3390/microorganisms9051010
|View full text |Cite
|
Sign up to set email alerts
|

Different csrA Expression Levels in C versus K-12 E. coli Strains Affect Biofilm Formation and Impact the Regulatory Mechanism Presided by the CsrB and CsrC Small RNAs

Abstract: Escherichia coli C is a strong biofilm producer in comparison to E. coli K-12 laboratory strains due to higher expression of the pgaABCD operon encoding the enzymes for the biosynthesis of the extracellular polysaccharide poly-β-1,6-N-acetylglucosamine (PNAG). The pgaABCD operon is negatively regulated at the post-transcriptional level by two factors, namely CsrA, a conserved RNA-binding protein controlling multiple pathways, and the RNA exonuclease polynucleotide phosphorylase (PNPase). In this work, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…CsrA, the global carbon storage regulator, is also a regulator of biofilm formation, which is controlled at the level of transcription and post-transcriptionally, both by indirect and direct mechanisms ( Jackson et al., 2002 ; Mitra et al., 2013 ). Two small ncRNA, namely, CsrB and CsrC, bind to CsrA and sequester its activity ( Carzaniga et al., 2021 ).…”
Section: Biofilm Regulation By Non-coding Rna In Gram-negative Bacteriamentioning
confidence: 99%
“…CsrA, the global carbon storage regulator, is also a regulator of biofilm formation, which is controlled at the level of transcription and post-transcriptionally, both by indirect and direct mechanisms ( Jackson et al., 2002 ; Mitra et al., 2013 ). Two small ncRNA, namely, CsrB and CsrC, bind to CsrA and sequester its activity ( Carzaniga et al., 2021 ).…”
Section: Biofilm Regulation By Non-coding Rna In Gram-negative Bacteriamentioning
confidence: 99%
“…The Csr regulatory system is highly conserved among many pathogenic bacteria, including Pseudomonas aeruginosa , Salmonella Typhimurium and Yersinia pseudotuberculosis, where it controls biofilm formation and virulence mechanisms [ 33 , 34 , 35 ]. Surprisingly, a recent study comparing E. coli C and E. coli K12 discovered that the levels of CsrB and CsrC are much higher in the K12 strain than in the C strain [ 36 ]. This is an apparent contradiction, since E. coli C is naturally much more prone to produce biofilms than the E. coli K12 strains and, as such, it would be expected that the levels of these sRNAs would be higher in the C strain.…”
Section: Rna Regulatory Mechanisms That Affect Biofilm Formationmentioning
confidence: 99%
“…This is an apparent contradiction, since E. coli C is naturally much more prone to produce biofilms than the E. coli K12 strains and, as such, it would be expected that the levels of these sRNAs would be higher in the C strain. In fact, the authors found that in E. coli C, there is no compensatory regulation similar to the one that exists between CsrB and CsrC in E. coli K12 strains [ 36 ]. This difference between two E. coli strains is a clear example that although the same systems are conserved among bacteria it should not be assumed that their function is equal.…”
Section: Rna Regulatory Mechanisms That Affect Biofilm Formationmentioning
confidence: 99%
“…This base pairing alters mRNA stability or translation, thus results in inhibition or activation of target gene expression. Nonetheless, there are some sRNAs act through interactions with regulatory proteins directly, e.g., the RNA component of the ubiquitous signal recognition particle (SRP), and sRNA CsrB/CsrC that sequester small protein CsrA [3][4][5] . Up to now, all of the bacterial noncoding RNAs are reported functioning through linear forms.…”
Section: Introductionmentioning
confidence: 99%